Influence of Cold Metal Transfer Process and Its Heat Input on Weld Bead Geometry and Porosity of Aluminum-Copper Alloy Welds. Issue 3 (March 2016) - Cong, Baoqiang; Ouyang, Ruijie; Qi, Bojin; Ding, Jialuo
Abstract: The weld bead geometry and the porosity of AA2219-T851 high strength aluminum alloy welds with ER2319 wire produced by different cold metal transfer (CMT) processes and heat inputs were investigated. The results show that a narrow finger-shaped geometry is observed using the conventional CMT process and a large number of gas pores exist in the lower and upper parts of welds. Compared to results of above mentioned CMT process, the weld melting area is increased using CMT-pulse (CMT-P) process, and it is beneficial to reduce the porosity effectively with an appropriate heat input. The finger-shaped geometry with lower melting depth using CMT-advanced (CMT-ADV) process and the spherical-shaped bead geometry with lower dilution using CMT-pulse advanced (CMT-PADV) process are achieved. The gas pore is reduced predominantly and even eliminated due to the lower heat input and the effective oxide cleanliness of wire ends for the two processes.